An Examination of the Role of the Companions in Early Hadith Forgery - Ulum, Muhammad Babul (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
The role that the Prophet's companions played in the campaign to fake hadiths is investigated in this article. There are two competing opinions regarding the genesis of the appearance of fake hadith, while both agree that political factors are the fundamental trigger. According to the first opinion, since the beginning of Islam, there have been incorrect hadith. The first group of Muslims, the Companions of the Prophet, are the ones who are at fault. The majority of Western Revisionist academics, led by Goldziher and Schacht, agree with this viewpoint; non-mainstream Islamic scholars, such Ahmad Amin and Abu Rayyah, endorse it. On the other hand, mainstream Islamic scholars, led by Muhammad Mustafa Azami, disagree, citing the Companions’ justification (‘adalah al-sahabah). This article attempts to evaluate the arguments using the abductive method. Opinions that correspond to the data are taken, which are contrary to the rejection. It follows that the view that the Companions were complicit in the hadith’s falsification is the one that is more grounded in scientific evidence. Conversely, the viewpoints that dispute it are founded solely on the widely accepted Companions’ conception of justice, which is better described as dogma than actual scientific knowledge.